Investigating the Effects of Optimized Mineral Fertilization on Plant Growth, Physiological Traits, Tuber Yield, and Biochemical Contents of Potato Crop - Hadjer Chabani; Neji Tarchoun; Roua Amami; Wassim Saadaoui; Najla Mezghani; Alexios A. Alexopoulos; Spyridon A. Petropoulos (Horticulturae)
Plants of two potato (Solanum tuberosum L.) varieties ‘Spunta’ (mid-early maturity) and ‘Kensa’ (mid-late maturity) were subjected to three nitrogen (N), phosphorus (P), and potassium (K) fertilization regimes, with T1 optimal rates (as recommended by the Tunisian Potato Technical Centre), T2 high rates (+25% of T1), and T3 low rates (−25% of T1). Plant growth, yield components, chlorophyll fluorescence (Fo, Fm, Fv/Fm), photosynthetic active radiation (PAR), real evapotranspiration (RET), and biochemical parameters in mature leaves and tubers (total soluble sugars (TSSs) and starch in both leaves and tubers) were evaluated. Our results showed a significant effect of fertilizer rates on plant growth, physiological, yield, and quality traits, as well as on biochemical contents of leaves and tubers, as well as on the variety. The application of high rates (T2) resulted in increased chlorophyll fluorescence (Fo) and high ratios of Fv/Fm, and it reduced Fm and photosynthetic active radiation (PAR). The highest yield per plant (615.4 g of tubers) and average number of tubers/plant (6.44) were observed in cv. ‘Spunta’ subjected to optimal fertilizer rate (T1), while more than 50% of tubers of this variety were classified as size C1 (>50 mm). On the other hand, high rates (T2) increased the yield per plant (436.74 g; approximately 9.3% compared to T1) and the number of tubers per plant (5.70) in cv. ‘Kensa’, with approximately 56% of tubers being classified in the C1 category. High rates also increased sucrose and starch content in tubers, regardless of the variety, without being significantly different from the other fertilization regimes. In conclusion, our results provide important information regarding the effect of fertilization practice on potato growth and yield parameters and the biochemical composition of leaves and tubers. Therefore, it could be suggested that the application of reduced NPK rates (−25% of optimal rates) in mid-early varieties (namely cv. ‘Spunta’) could reduce the production cost without compromising yield and quality components.